Aorto-duodenal fistula: a rare but serious complication of gastrointestinal hemorrhage. A case report - Šumskienė, Jolanta; Šveikauskaitė, Edita; Kondrackienė, Jūratė; Kupčinskas, Limas (Acta medica Lituanica, 2016)
A primary aortoduodenal fistula (PADF) is a rare cause of gastrointestinal bleeding that is difficult to diagnose (and sometimes not diagnosed until a laparotomy.) A PADF is associated with high mortality if undiagnosed and untreated (the mortality rate of nearly 100% in the absence of a surgical intervention). While this condition is extremely rare with an incidence rate at autopsy of 0.04% to 0.07%, a secondary ADF occurs much more commonly (the post-operative incidence of 0.5% to 2.3%) and is due to prior aortic surgery and/or the placement of a synthetic aortic graft. It should be considered in any elderly patient who presents with upper gastrointestinal bleeding in the context of a known abdominal aortic aneurysm or without it when no identifiable source of bleeding is found. We present an autopsy case of a 59-year-old man with no history of an abdominal aortic aneurysm who presented with intermittent massive gastrointestinal bleeding. The autopsy revealed a pinhole fistula. It was identified between an atherosclerotic abdominal aortic aneurysm and the lower horizontal part of the duodenum. Our case indicates that the aortoenteric fistula can result in fatal gastrointestinal bleeding. This case is unique in that the fistula formed as a result of a complex atherosclerotic abdominal aorta and a localized necrotizing granulomatous aortitis the etiology of which was not clear.